2011
DOI: 10.1002/j.2050-0416.2011.tb00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Perspectives in Gushing Analysis: A Review

Abstract: The phenomenon of gushing, characterized by the spontaneous overfoaming of carbonated beverages directly after opening a bottle (or a can), can still be a problem for the brewing and beverage industry worldwide. Due to its sudden and partly eruptive character, gushing can be detrimental to the image of the industry when it occurs in the hands of the consumer. Gushing is a complex phenomenon, induced by a variety of gushing factors of the raw materials and in the production process. A reliable methodology to av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…Besides the financial problems, the customer's desire to completely change the brand after a gushing experience contributes to the overall negativity towards this phenomenon. Note that gushing is not limited to only beer, but is a well-known occurrence in the carbonated beverages industry (fruit sodas, sparkling wines, champagnes, lemonades, and mineral water) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the financial problems, the customer's desire to completely change the brand after a gushing experience contributes to the overall negativity towards this phenomenon. Note that gushing is not limited to only beer, but is a well-known occurrence in the carbonated beverages industry (fruit sodas, sparkling wines, champagnes, lemonades, and mineral water) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium species are known producers of mycotoxins, but they also excrete hyrophobins that cause gushing [35,[76][77][78][79][80][81]. Gushing can be described as uncontrolled, eruptive foaming of beer after a bottle has been opened, without previous shaking or any agitation (Figure 4).…”
Section: Gushing-an Important Economic Factormentioning
confidence: 99%
“…Most of FCR studies were focused on wheat, however, also barley through the years increased its importance, in parallel with the increase of the economic relevance of malt industry with the establishment of new microbreweries, especially in Italy (The Brewers of Europe 2015). Fungi belonging to the genus Fusarium represent unwanted microorganisms for the quality of final malt and beer as well as for beer consumers' health due to mycotoxin contamination related to their presence (Sarlin et al 2005, Wolf-Hall 2007, Christian et al 2011, Oliveira et al 2013, Bertuzzi et al 2011, Hückelhoven et al 2018. Furthermore, one of the main concerns of the malt industry is the gushing phenomenon (Garbe et al 2008), which, as reported by some authors, seems to be influenced by the presence of hydrophobins produced by FHB pathogens (Sarlin et al 2005, Nielsen et al 2014.…”
Section: Manuscript Received December 2017mentioning
confidence: 99%